Protrusion of the lung apex through Sibson's fascia in infancy. Issue 3 (June 1978) - Grunebaum, M; Griscom, N T
Abstract : Apical 'herniation' of the lung is an unusual protrusion of the lung and its pleural coverings through the superior aperture of the thorax. It is supposedly caused by weakness of Sibson's fascia. The phenomenon is an anatomical variation and not a disease entity; however, it must be recognised in order to avoid inappropriate surgery. The condition apparently disappears spontaneously with growth.